2022
DOI: 10.1249/01.mss.0000877628.51947.fc
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extensor Rate Of Torque Development Assessment Post-acl Reconstruction: Does Sampling Rate Matter?

Abstract: Low 0.005 ± 0.014 0.006 ± 0.015 High ✕ Symmetrical 0.007 (0.001, 0.01) 0.02* Symmetrical -0.001 ± 0.009 -0.004 ± 0.10 Low ✕ Symmetrical 0.008 (0.002, 0.01) 0.01* *Indicates a significant condition main effects; Body Weight (BW); Standard Deviation (SD); Confidence Interval (CI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, it was beyond the scope of this study to consider the effects of psychological factors, neural factors, and other muscular properties that could influence performance of the ACL-injured limb. Finally, RTD measures were collected at 100 Hz, which is lower than the recommended 1,000 Hz; however, recent work found high agreement between RTD measures at high and low sampling rates (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was beyond the scope of this study to consider the effects of psychological factors, neural factors, and other muscular properties that could influence performance of the ACL-injured limb. Finally, RTD measures were collected at 100 Hz, which is lower than the recommended 1,000 Hz; however, recent work found high agreement between RTD measures at high and low sampling rates (6).…”
Section: Discussionmentioning
confidence: 99%
“…Rate of torque development was calculated as the slope of the torque time curve from 0 to 100 ms and 100 to 200 ms (Figure 1) (12,20). Recent work has shown that there is strong correlation between RTD sampled at 100 and 2000 Hz for the investigated time phases of 0-100 ms and 100-200 ms (6). Sampling RTD at 100 Hz may also be more clinically feasible because this is the standard sampling frequency of commercial isokinetic dynamometers.…”
Section: Methodsmentioning
confidence: 99%